Effective Targeted Photothermal Ablation of Multidrug Resistant Bacteria and Their Biofilms with NIR‐Absorbing Gold Nanocrosses. Issue 16 (23rd June 2016) - Teng, Choon Peng; Zhou, Tielin; Ye, Enyi; Liu, Shuhua; Koh, Leng Duei; Low, Michelle; Loh, Xian Jun; Win, Khin Yin; Zhang, Lianhui; Han, Ming‐Yong
Abstract : With the rapid evolution of antibiotic resistance in bacteria, antibiotic‐resistant bacteria (in particular, multidrug‐resistant bacteria) and their biofilms have been becoming more and more difficult to be effectively treated with conventional antibiotics. As such, there is a great demand to develop a nonantibiotic approach in efficiently eliminating such bacteria. Here, multibranched gold nanocrosses with strong near‐infrared absorption falling in the biological window, which heat up quickly under near‐infrared‐light irradiation are presented. The gold nanocrosses are conjugated to secondary and primary antibodies for targeting PcrV, a type III secretion protein, which is uniquely expressed on the bacteria superbug, Pseudomonas aeruginosa . The conjugated gold nanocrosses are capable of completely destroying P. aeruginosa and its biofilms upon near‐infrared‐light irradiation for 5 min with an 800 nm laser at a low power density of ≈3.0 W cm −2 . No bacterial activity is detected after 48 h postirradiation, which indicates that the heat generated from the irradiated plasmonic gold nanocrosses attached to bacteria is effective in eliminating and preventing the re‐growth of the bacteria. Overall, the conjugated gold nanocrosses allow targeted and effective photothermal ablation of multidrug‐resistant bacteria and their biofilms in the localized region with reduced nonspecific damage to normal tissue. Abstract : Multiple branched gold nanostructures with strong near‐infrared absorption are synthesized and conjugated with primary and secondary antibodies for effective targeted photothermal ablation of multidrug‐resistant bacteria, which have become increasingly difficult to be treated with clinically available antibiotics. This method improves the efficiency in eliminating bacteria/biofilms and offers flexibility by changing the corresponding primary antibodies to target other bacteria strains.